Schottky Uniformizations of Z22 Actions on Riemann Surfaces - A. Hidalgo, Rubén (Revista Matemática Complutense, 2005)
Given a closed Riemann surface S together a group of its conformal automorphisms H _= Z22 , it is known that there are Schottky uniformizations of S realizing H. In this note we proceed to give an explicit Schottky uniformizations for each of all different topological actions of Z22 as group of conformal automorphisms on a closed Riemann surface.